Virtual Approach to Ground Armoured Vehicles Design (Advances in Military Technology, 2022)
The paper deals with computer based design tools and processes integration in the development of ground armoured vehicles. The general demands for ground vehicles and for their development are determined by the environment in which they operate. The paper aims at giving the design process of armoured vehicles overview as well as some insight into specific topics important in the process and describes the integration of modelling and simulation into the virtual process, vehicle dynamics, suspension design, mobility, and mine protection using new armoured vehicles.
Keywords: virtual prototypes; integration; design process; calculations; development process; modelling and simulation tools